The contemporary British novel since 2000 - Acheson, James, 1947- (Edinburgh University Press, 2017)
"The Contemporary British Novel Since 2000 is in five parts, with the first part examining the work of four particularly well-known and highly regarded twenty-first century writers: Ian McEwan, David Mitchell, Hilary Mantel and Zadie Smith. It is with reference to each of these novelists in turn that the terms 'realist', 'postmodernist', 'historical' and 'postcolonialist' fiction are introduced, while in the remaining four parts, other novelists are discussed and the meaning of the terms amplified. From the start it is emphasised that these terms and others often mean different things to different novelists, and that the complexity of their novels often obliges us to discuss their work with reference to more than one of the terms. Also discusses the works of: Maggie O'Farrell, Sarah Hall, A.L. Kennedy, Alan Warner, Ali Smith, Kazuo Ishiguro, Kate Atkinson, Salman Rushdie, Adam Foulds, Sarah Waters, James Robertson, Mohsin Hamid, Andrea Levy, and Aminatta Forna."--